(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s
(3ChdgG (B:s
(3GdQcf GdKGdK ef eYJeO gPG GdcJGH aj GdWgGQI GdJQGHjI(B...s
(3BNQgG (B:s
(3jfJgj HBNQ GdcdGe aj GdJjee(B: ...(3fYe XGgQ GdeQSd EfeG gh aj GdJjee ddeMOK HGdCUZQ hEf CWdb GdWgGQI aj UOQg ceG Cf XGgQg aj ZjQ GdeJYeO JQc GdhVhA aGdJYeje ddCeQjf eMJGL Edi Odjd BNQ ZjQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B92s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B378s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis